Surface characteristics and antimicrobial properties of modified catheter surfaces by polypyrogallol and metal ions - Balne, Praveen Kumar (2018)
Catheter associated infections (CAIs) are the major cause of nosocomial infections leading to increased morbidity, mortality rates and economical loss. Though the antibiotic coated surface modified catheters are reported to be effective in preventing CAIs, presence of sub-lethal concentrations of antibiotics in long term instilled catheters poses a risk of development and spread of drug resistant microbial strains. Herein, we have developed an antibiotic-free alternative strategy to coat catheter surfaces using pyrogallol (PG) and metal ions (Ag+/Mg2+). Surface characteristics, antimicrobial and anti-biofilm properties with hemocompatibility of the coated catheters were studied. Structural characteristics of coated catheters were similar to the uncoated catheters with improved wettability. All the coated catheters with PG and different PG/metal ion combinations exhibited broad spectrum antibacterial activity. Catheters coated with PG/metal ions combination showed effective antibiofilm properties against MRSA strains. None of the coated catheters showed any significant hemolysis for rabbit erythrocytes. In addition, polypyrogallol (pPG) coating attenuated the hemolytic properties of silver without altering the antimicrobial properties. The inherent antimicrobial properties of the coating agent along with antimicrobial metal ions broaden the application landscape which includes coating of other medical devices, clean room construction and development of antimicrobial surfaces. The chemical formulation can also be used to design antiseptic solutions to prevent healthcare associated infections.